Knowledge and utilization of family planning methods among people living with HIV in Kathmandu, Nepal - Rajani Pokharel; Geeta Bhattarai; Namuna Shrestha; Sharad Onta (BMC, 2018)
Abstract Background Addressing family planning (FP) needs of people living with HIV is an effective response to HIV prevention. Healthy timing and spacing of births help ensure the health and well-being of all women and infants, regardless of their HIV-infection. In addition, preventing unintended pregnancies is an important strategy for prevention of mother to child transmission of HIV. The main purpose of this study was to explore the knowledge of family planning methods and identify factors affecting the utilization of such methods among HIV infected men and women attending two Anti-Retroviral Therapy (ART) sites of Kathmandu, Nepal. Methods This was a descriptive cross-sectional study. Two ART sites of Kathmandu were purposively chosen and a sample of 265 respondents (both men and women) was selected based on proportionate probability random sampling. A structured questionnaire was administered face to face to all of the eligible participants. Results The mean ± SD age of the participants was 36.62 ± 7.58 years. Sixty five percent of the respondents' spouses were HIV positive. A majority of the respondents (72%) had heard of seven modern family planning methods. Considerably high number (72%) of the respondents or their spouses were using at least one of the method of family planning. The most common method was condom (83%) and the least common was IUCD (0.50%). The use of short acting (pills, depo-provera) and long acting (implant, IUCD) family planning methods other than condom dropped from 56.6 to 2% after diagnosis. Utilization of family planning methods was significantly associated with gender, education and HIV status of spouse. Males (Adjusted Odds Ratio (AOR) = 2.48, 95% CI = 1.20-5.07, p = 0.01) educated respondents (AOR = 3.27, 95% CI = 1.41-7.54, p = < 0.01) and individuals whose spouse were not infected with HIV (AOR = 4.70, 95% CI = 1.41-15.67, p = 0.01) were more likely to use FP methods. Conclusion The tendency for HIV infected men and women to avoid additional child bearing in Nepal is higher compared to sub-Saharan Africa. However, the use of effective methods of family planning is low. Therefore, more effective counselling sessions by service providers regarding the availability and use of alternative family planning methods besides condom is necessary.